Comparison of British and French expatriate doctors’ characteristics and motivations - Quantin, Catherine; Abbas, Rachid; Hagi, Mathieu; Breton, Gwenaelle Le; Romestaing, M; Carnet, Dider (BMJ Open, 2012)
Objective The aim of this study was to analyse the migration of doctors between the UK and France, in an attempt to identify the reasons for these migrations. Design This was a cross-sectional study conducted using a self-completed questionnaire. Setting The questionnaire was sent to all British doctors practising in France and to all French doctors practising in the UK. Participants The doctors were identified, thanks to official data of the National Medical Councils. There were 244 French doctors practising in the UK and 86 British doctors practising in France. Outcome measures A questionnaire was specifically developed for the study to determine the reasons why doctors moved to the other country and their level of satisfaction with regard to their expatriation. Results A total of 98 French doctors (of 244) and 40 British doctors (of 86) returned the questionnaire. The motivations of the two studied populations were different: French doctors were attracted by the conditions offered by the National Health Service, whereas British doctors were more interested in opportunities for career advancement, moved to join a husband or wife or to benefit from favourable environmental conditions. Overall, the doctors who responded considered the expatriation a satisfactory experience. After expatriation, 84% of French doctors were satisfied with their new professional situation compared with only 58% of British doctors. Conclusions This study, which is the first of its kind and based on representative samples, has led to a clearer understanding of the migration of doctors between France and the UK.